The Reflections of Modernization in Turkey on the Architectural Artifacts of Izmir Culturepark Between 1930-1950 - Pöğün, Yüksel; Eyüce, Emine Özen (Izmir Institute of Technology, 2000)
This study aims to analyze the movements of modern architecture following the foundation of the Turkish Republic, through the Culturepark in izmir. The analyses will cover the period between 1930 and 1950, starting with the foundation of the Turkish Republic and covering the initial planning phase of the izmir Fair and Culturepark idea.The modernisation and Westernization trends in architecture in Turkey during the specified period are observed in the izmir Culturepark. The political ideology, involving the attributes of the single party system, and the prevailing economical conditions, reflecting the state socialism approach, had important influence on the changing understanding in architectural expression. These reflections concern both the inclusion of the Culturepark in the urban design of izmir and the temporary pavilion buildings designed and constructed for the izmir International Fair. These characteristics make the izmir Fair different from comparable InternationalFairs of the World and give a unique identity: The International Fair in izmir of Turkey. Furthermore, in addition to providing a medium to display the technological advancements of the time, like other similar fairs, the izmir International Fair has been aimed to be a demonstration of the political, social, or economicpower of a nation, that has just conquerred the war independence. The objective of the Fair was to show the world and the citizens of Turkey, the determination of the young Turkish Republic in modernisation through reforms.Analyzing the form and design characteristics of architectural artifacts in the izmir Culturepark will reflect the existing architectural understanding of the period as well as providing insights relating to future developments.
Thesis (Master)--İzmir Institute of Technology, Architecture, İzmir, 2000
Includes bibliographical references (leaves: 124-130)
Text in English; Abstract: Turkish and English
xiv, 145 leaves
Keywords: NA680 .P64 2000; Arhitecture, Modern--20th century; Modern movement (Arhitecture); Arhitecture--Turkey--İzmir; Fairs--Turkey--History